1988
DOI: 10.1111/j.1399-3054.1988.tb09155.x
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory energy costs for the maintenance of biomass, for growth and for ion uptake in roots of Carex diandra and Carex acutiformis

Abstract: Respiratory energy costs for the maintenance of biomass, for growth and for ion uptake in roots of Carex diandra and Carex acutiformis. -Physiol. Plant. 72: 483491.The respiratory characteristics of the roots of Carex diandra Schrank and Carex acutiformis Ehrh. were investigated. The aims were, firstly to determine the respiratory energy costs for the maintenance of root biomass, for root growth and for ion uptake, and secondly to explain the higher rate of root respiration and ATP production in C. diandra. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
87
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(93 citation statements)
references
References 27 publications
5
87
1
Order By: Relevance
“…A great decrease in ATP/ADP level and energy charge was detected in Sinapis alba seeds treated by sunflower leaf allelochemicals (Bogatek et al 2002). Ion uptake and growth are the most energy-consuming processes in plant cells (Van der Werf et al 1988). Inhibition of seedling growth in allelopathy stress conditions may be therefore a result of decreased ion uptake.…”
Section: Resultsmentioning
confidence: 99%
“…A great decrease in ATP/ADP level and energy charge was detected in Sinapis alba seeds treated by sunflower leaf allelochemicals (Bogatek et al 2002). Ion uptake and growth are the most energy-consuming processes in plant cells (Van der Werf et al 1988). Inhibition of seedling growth in allelopathy stress conditions may be therefore a result of decreased ion uptake.…”
Section: Resultsmentioning
confidence: 99%
“…60 d of root maintenance in unfavorable conditions would cost as much as one cycle of root death followed by regrowth. Van der Werf et al (1988) showed, for a different species, that the ATP costs of producing 1 g f. wt of root is approximately equal to the cost of maintaining 1 g of root for 10 d. It might therefore actually be more energetically expensive to maintain fine roots when the costs of maintenance during periods of stress exceed the costs of constructing new roots upon the return of more favorable soil conditions.…”
Section: Costs and Benefits Of Root Turnovermentioning
confidence: 99%
“…Although increasing resource allocation to root growth improves P acquisition, unbalanced root development reduces overall plant growth due to the increased metabolic cost of added root tissue (Nielsen et al, 1998(Nielsen et al, , 2001Lambers et al, 2006). Over 50% of daily carbon fixation may be consumed by the root system, with P-stressed plants allocating a larger fraction of their daytime net carbon assimilation than nonstressed plants (Van Der Werf et al, 1988;Lambers et al, 1996;Nielsen et al, 1998Nielsen et al, , 2001). This cost consists of three main components: the growth of new root tissue, ion uptake and assimilation, and the maintenance of existing root tissue (Nielsen et al, 1998;Fan et al, 2003).…”
mentioning
confidence: 99%